Multicopter Design Optimization and Validation - Øyvind Magnussen; Morten Ottestad; Geir Hovland (Modeling, Identification and Control, 2015)
This paper presents a method for optimizing the design of a multicopter unmanned aerial vehicle (UAV, also called multirotor or drone). In practice a set of datasheets is available to the designer for the various components such as battery pack, motor and propellers. The designer can not normally design the parameters of the actuator system freely, but is constrained to pick components based on available datasheets. The mixed-integer programming approach is well suited to design optimization in such cases when only a discrete set of components is available. The paper also includes an experimental section where the simulated dynamic responses of optimized designs are compared against the experimental results. The paper demonstrates that mixed-integer programming is well suited to design optimization of multicopter UAVs and that the modeling assumptions match well with the experimental validation.